Sanctions for Criminal Acts Without the Right to Use Academic Degrees, Vocational Degrees and Professional Degrees According to Law No. 12 of 2012 concerning Higher Education (Study at the Supreme Court of the Republic of Indonesia) - Nurhayati, Lilis; Hartini, Sri; Ratnawaty, Latifah (JURNAL MAHASISWA YUSTISI, 2023)
An academic degree is a degree obtained through a certain level of education, in a certain field as well. Examples of this academic degree are S, Pd for education, (S.T) for engineering, (S, Ag) for religion, (Dr) for health, and others. A vocational degree is a degree given to diploma-level graduates of vocational education or academies that produce expertise in a particular field from a university. Professional degree A professional degree is a degree given to graduates of professional education in a particular field of study from a university. The conclusion obtained from the research is that the inclusion of a false academic degree for a person for the sake of public recognition, that a person has a high educational background, which is indicated by a degree can be subject to criminal sanctions. The legislation regulates the prohibition of degrees used without rights by a person, this is in accordance with the formulation of article 28 paragraph (7) of law No. 12 of 2012 concerning higher education which reads "individuals who without rights are prohibited from using academic degrees, vocational degrees and / or professional titles. Keywords: Academic Degree, Vocational Degree and Professional Degree